Health Education Against Changes in Physical Activity Patterns and Body Mass Index - Asnidar; Muriyati; Asri; Safruddin; Haerani; Hamdana (Postgraduate, University of Mataram, 2023)
Obesity problems in children will be at high risk of obesity in adulthood and potentially experience various causes of significant risks for some chronic diseases associated with diets, such as type 2 diabetes mellitus, hypertension, stroke, cardiovascular disease, and certain types of cancer.This research aims to determine the effect of health education based on social media to the pattern of physical activity and body mass index (BMI) adolescent overweight and obesity of each group and between groups in Bulukumba, Indonesia. The design of this research is the